RELEVANSI PEMIKIRAN FILSAFAT ISLAM PERSPEKTIF MUHAMMAD IQBAL TERHADAP PENDIDIKAN ISLAM DI ERA MODERN - Febi Febrianda; Nunu Burhanuddin (CV. ADIBA ASIHA AMIRA, 2025)
This study examines the relevance of Muhammad Iqbal's Islamic philosophical thought to Islamic education in the modern era. Iqbal, as one of the greatest thinkers of the Islamic world, made a significant contribution to the understanding of the relationship between religion, education, and intellectual progress. In his view, education is not only aimed at creating technically skilled individuals, but also to shape character and deepen spirituality. Iqbal's thought emphasizes the importance of integration between science, faith, and the formation of self-awareness (selfhood) in the Islamic context. This paper will identify several key concepts in Iqbal's educational philosophy, such as the concept of